Relationships between grip power index and club head speed among NCAA Division I female golfers - Franklin, W.; Sun, D.; Durbin, K.; Smith, D. B. (International Journal of Exercise Science Conference Proceedings, 2024)
Power plays a significant role in determining a player`s golf performance. Greater power generates higher club head speeds, an integral aspect of carry distance. An advantage of improving club head speed by one mile per hour is that it results in roughly two to three yards of additional carry distance.